One-Pot Synthesis of 3,4-Dihydropyrimidine-2(1H)-thione Derivatives Using DBU as Green and Recyclable Catalyst - Sekhar, T.; Thriveni, P.; Harikrishna, M.; Murali, K. (Asian Journal of Chemistry, 2018)
A short and simple one-pot synthesis of 3,4-dihydropyrimidine-2(1H)-thione derivatives was accomplished in excellent yields by reaction of aryl ketone, aryl aldehydes and thiourea in aqueous ethanol (50 %) using 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) as a reusable catalyst.